Developmental effects of sulfated thyroid hormones in sea urchin skeletogenesis suggest activation of non-canonical thyroid hormone signaling pathway - Tieman, Katherine; Heyland, Andreas (Frontiers in Endocrinology, 2025)
Thyroid hormones (THs) are essential regulators of metabolism, homeostasis, and development in metazoans. The canonical genomic pathway involves THs binding to nuclear thyroid hormone receptors (NTHRs), which modulate gene expression in vertebrates. In contrast, non-genomic pathways involve THs interacting with membrane-bound or cytoplasmic receptors. One such pathway includes TH binding to the RGD-binding integrin dimer αVβ3, which activates the Mitogen-Activated Protein Kinase (MAPK) cascade, influencing cancer cell proliferation, metastasis, and angiogenesis. Both T4 and sulfated thyroid hormones (STHs) have been identified as actual and putative ligands in this pathway respectively. In the sea urchin Strongylocentrotus purpuratus, T4 and to a lesser extent T3 accelerate biomineralization—the formation of skeletal structures during embryonic and larval development—by modulating the activity of key transcription factors involved in this process. RGD peptides, potential ligands for the sea urchin integrin αPβG, can inhibit T4-induced effects, suggesting a role for integrin-mediated MAPK signaling (ERK1/2). This study examines whether STHs have developmental roles in sea urchin embryonic skeletogenesis and whether they bind to the αPβG integrin dimer in silico, a TH receptor candidate in sea urchins. Our findings show that STHs, like T4, accelerate the onset of skeletogenesis and increase the frequency of ectopic spicule formation, particularly near ectodermal cells. Homology modeling indicates that the αPβG integrin binds both T4 and STHs with high affinity, whereas no strong binding was observed between TH metabolites and the NTHR in sea urchins. We conclude that STHs have a developmental function in sea urchin skeletogenesis, likely mediated by the αPβG integrin rather than the NTHR. This represents the first documented developmental role of STHs and highlights the importance of non-canonical TH signaling in invertebrate development, encouraging further exploration of TH pathways in non-chordate animals.